Effect of cross-linking on physicochemical properties of tapioca starch and its application in soup product - Rungtiwa Wongsagonsup (2018)
Physicochemical properties of cross-linked tapioca starch (CLTS) with different cross-linking levels and their application as a thickening agent in soups were studied. The CLTS was prepared by cross-linking native tapioca starch suspended in alkaline solution (41.67% (w/w), pH 11) using a mixture (99:1 (w/w) ratio) of sodium trimetaphosphate (STMP) and sodium tripolyphosphate (STPP) at different concentrations ranged from 0.25% to 6.0% (w/w of starch) at 45 C for 3 h. Starch paste clarity decreased with increasing concentration of STMP/STPP mixture. Variations of swelling power, solubility, pasting, gelatinization, and rheological properties of the CLTS were found. Thermogravimetric analysis exhibited higher thermal stability for the CLTS granules compared to the native one. Among the samples, the CLTS prepared using 1.0% STMP/STPP (1.0%-CLTS) and soup containing the 1.0%-CLTS exhibited the strongest gel characteristic and the greatest shear resistant properties. The 1.0%-CLTS improved the textural properties and sensory quality of soups. © 2013 Elsevier Ltd.